IN VIVO INVESTIGATION OF HEPATOPROTECTIVE ACTIVITY OF ASTERACANTHA LONGIFOLIANEES. ON CCL INDUCED HEPATOTOXICITY IN WISTAR ALBINO RATS - MARIAPPAN, ANUSUYA; RAMALINGAM, SIVAKUMAR; SHAHUL HAMEED, SHEIKABDULLA; SARAVANAN, RENUKA (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objectives: This study was aimed to investigate the phytochemical constituents, antioxidant activity and hepatoprotective activity of Asteracantha longifolia leaf extract. Methods: Hepatotoxicity was induced in normal albino rats. Carbon tetrachloride (CCl 4 ) was administered orally at a dosage of 20 mg/kg body weight in physiological saline for 1 day. Group 1 served as Control. Group 2 served as disease control (CCl 20 mg/kg body weight). Group 3 served as animal treated with the aqueous extract A. longifolia (150 mg/kg body weight orally administered for 15 days). Group 4 served as animal treated with the aqueous extract A. longifolia (300 mg/kg body weight orally administered for 15 days). Group 5 served as animal treated with standard silymarin drug (20 mg/kg body weight orally administered for 15 days). After completed the experiment, the liver markers, lipid profile, and antioxidants were analyzed. 4 Results: Phytochemical screening of aqueous extract of A. longifolia leaves indicates the presence of flavonoids, tannins, glycosides, phenol, steroids, alkaloids, quinone, saponin, and coumarin. Supplementation of A. longifolia significantly restored the liver markers, lipid profile, and antioxidant markers on in CCl 4 induced Wistar albino rats. Conclusions: The results of our study showed that A. longifolia possess significant hepatoprotective and antioxidant activity, probably due to its phytochemicals. Keywords: Asteracantha longifolia, Phytochemicals, Carbon tetrachloride, Antioxidant.